PENINGKATAN KESADARAN MASYARAKAT TERHADAP DAMPAK SAMPAH LAUT DAN PENGELOLAANNYA MELALUI PENGENALAN KONSEP ECOBRICKS DI GUDANG ARANG, KELURAHAN BENTENG, KOTA AMBON - W. Tuahatu, Juliana; D. Manuputty, Gratia; Ch. Tuhumury, Novianty (HIRONO : Jurnal Pengabdian Masyarakat, 2022)
Gudang Arang community in Ambon City resides in a coastal area with a high population density. Traditional market activity is also existent. The public service program was conducted to increase people’s awareness of marine debris impact and introduce the eco-bricks concept as a practical way to reduce plastic waste from the environment. The program consisted of socialization, eco-bricks-making demonstration, discussion, and evaluation, including people’s knowledge and perspective on marine debris, its impact, and management. Based on the pre-socialization test, it was found that the knowledge about 3R of debris, waste banks, and mitigation concept of the people was low, i.e., 37.04%, 51.85%, 55.56%, respectively; whereas the concept of marine debris, its classification and impact were found good enough to very good (more than 70% to 96%). The perspective towards the presence of waste in the surroundings was excellent (more than 80%, however, the willingness to sort the waste before disposal was relatively low (no more than 70%). After the program, the evaluation increased the community’s knowledge compared to the pre-socialization ((96.30-100%). It implies that the socialization and concept demonstration such as eco-bricks-making and government’s support can positively influence the community in handling the waste